UPAYA MENINGKATKAN HASIL BELAJAR PKn DENGAN PENERAPAN MODEL KOPERATIF SKRIP SISWA KELAS VI SDN 005 BUKIT KAPUR KECAMATAN BUKIT KAPUR - Abdullah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low Civics learning outcomes of sixth-grade students at SDN 005 Bukit Kapur. This research aimed to describe improvements in student learning outcomes through the implementation of the Script Cooperative Learning Model. The subjects of the study were sixth-grade students at SDN 005 Bukit Kapur, and the research was conducted using a classroom action research design consisting of two cycles. The data in this study focused on the improvement of Civics learning outcomes. Data collection instruments included oral tests and written tests in the form of student worksheets administered after the learning process. The results of the study indicate that the application of the Script Cooperative Learning Model significantly improved student learning outcomes. The average learning absorption reached 93%, which is categorized as very good in Civics learning. Learning effectiveness was also categorized as very effective, with an average score of 93%. Furthermore, student learning completeness reached 100%, indicating that all students achieved mastery learning. These findings demonstrate that the cooperative script model is highly effective in improving Civics learning outcomes at the elementary school level.